Are questionnaires a reliable method to measure food waste? A pilot study on Italian households. Issue 12 (3rd December 2018) - Giordano, Claudia; Piras, Simone; Boschini, Matteo; Falasconi, Luca
Abstract : Purpose: The purpose of this paper is to assess the reliability of questionnaires as a method of quantifying household food waste (FW), thus providing context regarding the validity of existing Italian estimates. Design/methodology/approach: A total of 30 households were involved in a diary study that was conducted for one week. The participating households were first asked about their FW quantities in a questionnaire. Half of the households who filled their diaries properly were then audited through waste sorting analysis performed on their garbage. Non-parametric tests were used to test for differences in FW estimates between audited and non-audited households, as well as differences among estimates obtained through different quantification methodologies. Findings: Edible FW was estimated to be 489 grams per week based on questionnaires, and 1, 035 grams per week based on diaries. In the audited sub-sample of households, FW estimates were 334 grams per week based on questionnaires, 818 grams per week based on diaries and 1, 058 grams per week based on waste sorting analysis. Research limitations/implications: Given the small sample size in the present study, future studies can utilize larger samples to assess whether the differences identified in estimates can be replicated. Future studies can also inquire into the behavioral biases that led consumers to underestimate their FW. Practical implications: Results of the present study point against the use of questionnaires to quantify household FW, hence raising some doubt on the reliability of existent Italian estimates. Where waste sorting is unfeasible, the use of adjustment methods or diaries is suggested to better inform policies. Originality/value: This study is one of the first on FW quantification that tests three different methodologies on the same sample, and is the first to do so in Italy, where estimates are still very poor.